Social Engineering for Reducing Hypertension Case in Indonesia: a Qualitative Study in a Rural Area - Widyasari, Ratna; Pranata, Setia; Machfutra, Eka Denis; Pawitaningtyas, Indah; Kartika, Vita; Samosir, Jenny Veronica (Masyarakat Indonesia, 2023)
Consuming foods with a large amount of salt is an unhealthy lifestyle that raises blood pressure. People currently love salty foods in Indonesia. One of district in Indonesia called Jeneponto referred to hypertension as Nai’ Cera. The Jeneponto community consumes more significant salty food higher than the provincial average for South Sulawesi. An intervention study was carried out to change the habit of consuming high salt, smoking and drinking coffee. This study is qualitative with participatory action research approach. The in-depth interviews and focused group discussion were addressed to twenty-two informants which involved in an intervention program. Social engineering became the key-point to socialize the importance of the program. Well-trained local people recruited as an agent of change. They followed the social engineering intervention and focused on what people need to reduce hypertension. The program raised awareness on hypertension towards their lives by educating as well as discussing on their risky habits on over consumptions fatty, sugar, salt substances. The successful behavior changes in this program comprised several keys to consider such as: the intervention locations, the closest relationship towards the agent, the agent as frontliner, sustainability of the program, and commitment of all components of intervention.